2021
DOI: 10.1016/j.envpol.2020.116188
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol mitigated acute lung but not spermatic toxicity of C60 fullerene emulsion in mice

Abstract: C60 fullerene (C60) is a nano-pollutant that can damage the respiratory system. Eugenol exhibits significant anti-inflammatory and antioxidant properties. We aimed to investigate the time course of C60 emulsion-induced pulmonary and spermatic harms, as well as the effect of eugenol on C60 emulsion toxicity. The first group of mice (protocol 1) received intratracheally C60 emulsion (1.0 mg/kg BW) or vehicle and were tested at 12, 24, 72 and 96 h (F groups) thereafter. The second group of mice (protocol 2) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Other studies have found that for mice, the addition of EUG alleviated oxidative stress and acute lung toxicity induced by C 60 exposure, indicating that EUG can avoid functional changes and reduce lung tissue damage, which may be caused by EUG’s antioxidant potential through regulating the inflammatory process. 39 At the same time, it has been pointed out that EUG is a potential antibacterial compound against Salmonella typhi and can be used to prevent or treat S. typhi infection. 3 Lung cancer, the leading cause of cancer-related morbidity and mortality worldwide, remains a serious public health problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found that for mice, the addition of EUG alleviated oxidative stress and acute lung toxicity induced by C 60 exposure, indicating that EUG can avoid functional changes and reduce lung tissue damage, which may be caused by EUG’s antioxidant potential through regulating the inflammatory process. 39 At the same time, it has been pointed out that EUG is a potential antibacterial compound against Salmonella typhi and can be used to prevent or treat S. typhi infection. 3 Lung cancer, the leading cause of cancer-related morbidity and mortality worldwide, remains a serious public health problem.…”
Section: Resultsmentioning
confidence: 99%
“…That is to say, EUG has a protective effect against cadmium-induced toxicity, which is similar to the toxicological interaction attenuating effect of EUG found in this study. Other studies have found that for mice, the addition of EUG alleviated oxidative stress and acute lung toxicity induced by C 60 exposure, indicating that EUG can avoid functional changes and reduce lung tissue damage, which may be caused by EUG’s antioxidant potential through regulating the inflammatory process . At the same time, it has been pointed out that EUG is a potential antibacterial compound against Salmonella typhi and can be used to prevent or treat S.…”
Section: Resultsmentioning
confidence: 99%
“…In the lungs, C 60 induced morpho-functional and inflammatory hazards. Exposure to C 60 also damaged sperm cells and increased the risk of infertility [ 106 ]. Studies of Daphnia magna and zebrafish show that chronic C 60 exposure induced behavioral and physical abnormalities at concentrations at and over 5 mg/L and 2 mg/L, respectively [ 107 , 108 ].…”
Section: Factors Affecting Toxicitymentioning
confidence: 99%
“…Altogether it includes a hollow spherical cage-like structure with the unique ability to trap particles of size even in nanometers. The unique physical and chemical properties of fullerene have opened up tremendous usages in various essential areas like solar cells 3 , semiconductor (OSC) materials 4 , photocatalysts 5 , organic optoelectronic applications 6,7 , and biological and Biomedical applications respectively [8][9][10] . Buseck et al reported the occurrence of naturally occurring fullerene in the shungite rocks of Karelea 11 .…”
Section: Introductionmentioning
confidence: 99%